REALISASI PROJECT BASED LEARNING PADA PEMBELAJARAN SOSIAL EMOSIONAL - Sulastri (Jurnal Warna, 2022)
Social-emotional learning uses project-based learning, with the theme of work and the sub-theme of fishermen with core fishing activities. The learning media I use are fish, buckets, water, plastic cups, paper, pencils, scissors, glue and objects in the classroom. In Masyithoh Kroya Kindergarten, teaching and learning activities use learning media that is adapted to the Basic Curriculum (KD) that has been determined from schools to facilitate teaching and learning activities in order to achieve the expected goals. In addition to using media, teaching and learning activities use a group learning model, where groups of children in one day play in one class which contains 4 activities as fulfillment of 6 aspects of the scope of development. The activities prepared are: aspects of the development of religious and moral values, aspects of motor physical development, aspects of cognitive development, aspects of emotional social development, aspects of language development and aspects of art development